Geo-questionnaire: a spatially explicit method for eliciting public preferences, behavioural patterns, and local knowledge – an overview - Czepkiewicz, Michał; Jankowski, Piotr; Zwoliński, Zbigniew (Quaestiones Geographicae, 2018)
Geo-questionnaires have been used in a variety of domains to collect public preferences, behavioural patterns, and spatially-explicit local knowledge, for academic research and environmental and urban planning. This paper provides an overview of the method focusing on the methodical characteristics of geo-questionnaires including software functions, types of collected data, and techniques of data analysis. The paper also discusses broader methodical issues related to the practice of deploying geo-questionnaires such as respondent selection and recruitment, representativeness, and data quality. The discussion of methodical issues is followed by an overview of the recent examples of geo-questionnaire applications in Poland, and the discussion of socio-technical aspects of geo-questionnaire use in spatial planning.